Предмет: Алгебра,
автор: kira21112007
Решите уравнение 3 x ( 2 x − 3 ) = 2 6 + 2 x ( 3 x + 2 ) .
Ответы
Автор ответа:
1
Ответ:
исходное не пишу
6х²-9х=26+6х²+4х выделенное сократили
-9х-4х=26
-13х=26
х=26:(-13)
х=-2
Автор ответа:
1
Ответ:
6x^2-9x=26+6x^2+4x
6x^2-9x-6x^2-4x=26
-9x-4x=26
-13x=26
x=26÷(-13)
x= -2
Объяснение:
дай лучший ответ если помогла тебе
Похожие вопросы
Предмет: Русский язык,
автор: sazonova2372
Предмет: Обществознание,
автор: vaneeva05
Предмет: Литература,
автор: CaHbKa339
Предмет: Математика,
автор: Relr
Предмет: Математика,
автор: iddqd1996